Involvement of the LuxR-Type Transcriptional Regulator RamA in Regulation of Expression of the gapA Gene, Encoding Glyceraldehyde-3-Phosphate Dehydrogenase of Corynebacterium glutamicum - Toyoda, Koichi (American Society for Microbiology (ASM), 2009)
SugR, RamA, GlxR, GntR1, and a MarR-type transcriptional regulator bind to the promoter region of the gapA gene encoding glyceraldehyde-3-phosphate dehydrogenase (GAPDH), essential for glycolysis in Corynebacterium glutamicum. We previously showed that SugR, a transcriptional repressor of phosphotransferase system genes for the sugar transport system, is involved in the downregulation of gapA expression in the absence of sugar. In this study, the role of RamA in the expression of the gapA gene was examined. Comparing the gapA expression and GAPDH activity of a ramA mutant with those of the wild type revealed that RamA is involved in upregulation of gapA expression in glucose-grown cells. DNase I footprint analyses and electrophoretic mobility shift assays revealed that RamA binds with different affinities to three sites in the gapA promoter. lacZ reporter assays with mutated RamA binding sites in the gapA promoter showed that the middle binding site is the most important for RamA to activate gapA expression and that binding of RamA to the gapA promoter activates the gene expression not only in glucose-grown cells but also in acetate-grown cells. Furthermore, RamA also directly activates sugR expression, indicating that two global regulators, RamA and SugR, are coordinately involved in the complex regulation of gapA expression in C. glutamicum.